IL-4 and IL-17 Are Required for House Dust Mite-Driven Airway Hyperresponsiveness in Autoimmune Diabetes-Prone Non-Obese Diabetic Mice - Foray, Anne-Perrine; Dietrich, Céline; Pecquet, Coralie; Machavoine, François; Chatenoud, Lucienne; Leite-de-Moraes, Maria (Frontiers in Immunology, 2021)
Allergic asthma is characterized by airway inflammation with a Th2-type cytokine profile, hyper-IgE production, mucus hypersecretion, and airway hyperreactivity (AHR). It is increasingly recognized that asthma is a heterogeneous disease implicating complex immune mechanisms resulting in distinct endotypes observed in patients. In this study, we showed that non-obese diabetic (NOD) mice, which spontaneously develop autoimmune diabetes, undergo more severe allergic asthma airway inflammation and AHR than pro-Th2 BALB/c mice upon house dust mite (HDM) sensitization and challenge. The use of IL-4-deficient NOD mice and the in vivo neutralization of IL-17 demonstrated that both IL-4 and IL-17 are responsible by the exacerbated airway inflammation and AHR observed in NOD mice. Overall, our findings indicate that autoimmune diabetes-prone NOD mice might become useful as a new HDM-induced asthma model to elucidate allergic dysimmune mechanisms involving Th2 and Th17 responses that could better mimic some asthmatic endoytpes.